Variations Within Normal Hearing Acuity and Speech Comprehension: An Exploratory Study - Ayasse, Nicole D. (Am J Audiol, 2019)
PURPOSE: Many young adults with a mild hearing loss can appear unaware or unconcerned about their loss or its potential effects. A question that has not been raised in prior research is whether slight variability, even within the range of clinically normal hearing, may have a detrimental effect on comprehension of spoken sentences, especially when attempting to understand the meaning of sentences that offer an additional cognitive challenge. The purpose of this study was to address this question. METHOD: An exploratory analysis was conducted on data from 3 published studies that included young adults, ages 18 to 29 years, with audiometrically normal hearing acuity (pure-tone average < 15 dB HL) tested for comprehension of sentences that conveyed the sentence meaning with simpler or more complex linguistic structures. A product–moment correlation was conducted between individuals' hearing acuity and their comprehension accuracy. RESULTS: A significant correlation appeared between hearing acuity and comprehension accuracy for syntactically complex sentences, but not for sentences with a simpler syntactic structure. Partial correlations confirmed this relationship to hold independent of participant age within this relatively narrow age range. CONCLUSION: These findings suggest that slight elevations in hearing thresholds, even among young adults who pass a screen for normal hearing, can affect comprehension accuracy for spoken sentences when combined with cognitive demands imposed by sentences that convey their meaning with a complex linguistic structure. These findings support limited resource models of attentional allocation and argue for routine baseline hearing evaluations of young adults with current age-normal hearing acuity.